Generalization of the Behavior Sit in Canines to Novel Trainers - Miller, Jeffrey R.; Scharrer, Nicole C. (My University, 2010)
Generalization, in the context of training dogs, refers to a command controlling a behavior in novel environments or when given by a novel person (Mills, 2005). Stokes and Baer (1977) claim that generalization does not automatically occur, but active procedures need to be in place to ensure that the command will transfer to another trainer or environment. If trainers do not actively program for generalization, training would occur by only one trainer or by training the dog in one environment and hoping that the command will generalize to another trainer or environment. If trainers do actively program for generalization, training would occur by training different elements from other situations in which the dog will need to perform the behavior (e.g. train with multiple trainers, train in a different environment). The current study looks to determine if one trainer is sufficient, or if multiple trainers are necessary for dogs to generalize the command "sit" to a novel trainer.
Color poster with text and graphs.
Keywords: Dogs--Psychology; Dogs--Training; Posters; Learning, Psychology of